Case report on severe myelin oligodendrocyte glycoprotein antibody-associated disease relapse after ectopic pregnancy and laparoscopic medical abortion: relevance of peripheral inflammation for demyelinating disease activity - Smertinaite, Lidija; Selin, Katja; Vaitiniemi, Roosa; Balevicius, Ramojus; Kollia, Evangelia; Granberg, Tobias; Leite, Maria Isabel; Palace, Jacqueline; Blad, Helene; Karrenbauer, Virginija D. (Frontiers in Immunology, 2025)
BackgroundMyelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD) is a rare neurological condition. Tubal ectopic pregnancy is an important cause of maternal morbidity and mortality worldwide. Regular pregnancy has a disease-modifying effect on MOGAD, with an increased relapse rate postpartum. Still, there are neither case reports nor cohort studies on abortions and ectopic pregnancy as a disease-modifying event for MOGAD.Materials and methodsThis is a case report on a severe MOGAD relapse after ectopic pregnancy and laparoscopic abortion.DiscussionFor the first time we described that elevated interleukin-1 (IL-1), which was found in cerebrospinal fluid in the current case may be pathogenetically related to ectopic pregnancy. Rituximab (anti-CD20 treatment), downregulated IL-1 and TNF-alfa inflammatory pathways thus is an appropriate drug of choice to treat relapse. Cytokines secreted during ectopic pregnancy could play a disease-modifying role in multiple sclerosis and Guillian-Barré syndrome.ConclusionThe first case report of a MOGAD severe relapse after ectopic pregnancy and laparoscopic abortion which resolved with rituximab treatment.